Exchange Rate Risk Analysis Based on Firm Data: A Global Value Chain Perspective - Mimi Ning; Jianhong Qi (Discrete Dynamics in Nature and Society)
This paper investigates whether firms’ participation in the global value chain (GVC) weakens the exchange rate risk and its mechanism. Based on Powers and Riker’s (2013) expanding exchange rate risk model, this paper matches data from China’s refined input-output table, the customs database, and the industrial enterprise database from 2002 to 2009 to measure the firms’ GVC forward linkages and backward linkages and therefore empirically tests the relationship between participation in the GVC and the exchange rate risk. The results show that participation in the GVC reduces firms’ exchange rate risk through a “comovement effect” for forward linkages and a “hedging effect” for backward linkages; differences in a firm’s position in the GVC affect the extent of reduction in the exchange rate risk. Encouraging firms to participate in the GVC and strengthening GVC relationship with high-income countries in particular play an important role in minimizing the exchange rate risk.